Estimating the Cost of the Design, Production, and Dissemination of Social Media Videos for Social and Behavioral Change: Evidence From Merci Mon Héros in Niger and Côte d'Ivoire - Tchuenche, Michel; Bellows, Nicole; Portillo, Erin; Labati, Zamilatou H.; Adou, Denise B.; Hammond, Jacqueline; Silva, Martha; Bollinger, Lori (Frontiers in Public Health, 2021)
Merci Mon Héros (MMH) is a youth-led multi-media campaign in Francophone West Africa seeking to improve reproductive health and family planning outcomes using radio, television, social media, and community events. One component to this project is the development of a series of youth-driven videos created to encourage both youth and adults to break taboos by talking to each other about reproductive health and family planning. A costing study was conducted to capture costs associated with the design, production, and dissemination of 11 MMH videos (in French) on social media in Côte d'Ivoire and Niger. The total costs to design, produce and disseminate 11 of the campaign videos for MMH in both Côte d'Ivoire and Niger were 44,981. Unit costs were calculated using three different denominators, resulting in average unit costs of 0.16 per reach, 1.29 per engagement, and 4.27 per video view. These findings can be useful for future studies of SBC interventions using social media for framing the analysis and selecting the appropriate metrics for the denominator, as well as for budgeting and planning SBC programs using social media.